DOES ANYONE TALK ABOUT THE ISSUES ANYMORE? THE 2016 U.S. PRESIDENTIAL CANDIDATES’ MESSAGING ON FACEBOOK AND TWITTER - Stromer-Galley, Jennifer; Hemsley, Jeff; Rossini, Patricia; Smith, Alexander; Bolden, Sarah (AoIR Selected Papers of Internet Research, 2020)
As campaigns use social media to communicate with the public, this study investigates the dynamics of issue and image construction by the U.S. presidential candidates during the primary stage of the 2016 presidential campaign. Using computational techniques to classify candidate posts by message type and topic, we study all posts by the 17 Republican and 5 Democratic candidates from Sept. 1, 2015 through March 31, 2016. We ask whether candidates post more about their image–their character and personality–or on issues, and when they post on issues, does each candidate own specific policy issues. We also investigate which topics the public tends to engage with more. We also ask if there are differences in how the candidates use social media. Our results suggest that candidates post substantially less on the issues as compared with other types of messages. When they do post about policy topics, the candidates are associated with distinct policy positions, suggesting issue ownership as a strategic differentiator. Results also suggest campaigns use Facebook in ways different from Twitter, further reinforcing prior scholarship suggesting that campaigns use their social media for different purposes given different audiences on the platforms. Our findings indicate that campaigns overall are not discussing policy matters, thereby depriving the public the opportunity to engage in discussion of vital issues and what they would do to solve them; instead, the cult of personality seems to be further exacerbated by social media.